Upaya Membangun Sikap Kasih Dalam Hidup Keluarga Kristiani Diera Digital - Marike Amanda Adeltania Lewar; Intansakti Pius X (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
The influence of digital media is growing rapidly and influencing the lives of Christian families. The development of digital media has an impact on Christian families. Families have challenges in dealing with this situation. So Christian families need to rebuild a foundation that is able to meet the demands of the times and is in accordance with God's teachings. Building an attitude of love that can answer the needs of the times and is in line with God's teachings. The love that is built in a Christian family is Agape love. Agape love means total love, identified with God's love for His creation. An attitude of love is important for Christian families in everyday life. This article focuses on efforts to build an attitude of love in Christian families and the importance of an attitude of love for Christian families in the digital era. The implication of this research is to guide Christian families in using social media and technology responsibly. This includes monitoring the content consumed and maintaining Christian values ​​in interactions. This article uses a qualitative research method with a literature study approach. The data used in this article is secondary data from various sources such as books, articles and journals. Based on the research results, it was found that an attitude of love helps Christian families to maintain integrity and harmony in the digital era with healthy communication, using devices or applications that support togetherness and technology as a means of strengthening the quality of family relationships.